Synthesis and antibacterial activity of 1 beta-methyl-2-[5-(alpha,beta-disubstituted ethyl)pyrrolidin-3-ylthio]carbapenem derivatives. Part II - Kim, Jin-Woong; Park, Hyeong Beom; Chung, Bong Young; Lee, Jong Baek; Cho, Jung-Hyuck; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2006)
The synthesis of a new series of 1 beta-methylcarbapenems having 5-(alpha,beta-disubstituted ethyl)pyrrolidine moiety is described. Their in vitro antibacterial activities against both Gram-positive and Gram-negative bacteria were tested and the effect of substituents on the pyrrolidine ring was investigated. A particular compound (VIh) having alpha-hydroxy-beta-piperazinylethyl substituted moiety showed the most potent activity.
Keywords: BETA-LACTAM ANTIBIOTICS; CARBAPENEM ANTIBIOTICS; THIENAMYCIN; 1-BETA-METHYLCARBAPENEM